The Prolonged Drought in Australia: Causes, Impacts, and Mitigation Strategies - Christian Nate (International Journal of Science and Society, 2023)
Australia, often known as the "Land Down Under," is no stranger to extreme weather conditions, and one of the most persistent challenges it faces is prolonged droughts. This article explores the causes, impacts, and mitigation strategies related to the extended droughts experienced in Australia. By examining the complex interplay of natural factors and human activities, we can better understand the profound effects of these droughts and work towards sustainable solutions.